Quantitative study of Clostridium difficile transmission using extensive epidemiological data and whole genome sequencing - Eyre, DW (2013)
Clostridium difficile is a leading healthcare-associated infection, which causes diarrhoea, and is almost exclusively precipitated by antibiotic exposure. Traditionally C. difficile infection (CDI) has been considered predominantly transmitted within hospitals. However, endemic spread hampers identification of the source of infections, and therefore control and prevention of disease. A cohort of consecutive hospital and community CDI cases in Oxfordshire from September 2007 to March 2011 was investigated. For each case hospital admission, ward movement and demographic data were available allowing contact events between cases to be reconstructed. Initially 944 cases to March 2010 underwent multilocus sequence typing (MLST), subdividing the endemic cases into 69 distinct lineages and demonstrating unexpectedly that ward-based contact with known symptomatic CDI cases only accounts for <25% of disease. To better determine the extent of transmission arising from symptomatic patients, irrespective of the route transmission, isolates from 1223 cases to March 2011 underwent whole genome sequencing. Serially sampled patients with recurrent or on-going disease were used to estimate rates of C. difficile evolution and within-host diversity and to show 0-2 single nucleotide variants (SNVs) are expected between transmitted isolates obtained <124 days apart (95% prediction interval). Mixed infection with more than one strain was investigated, but probably plays only a minor role in onward transmission. In the Oxfordshire CDI cohort, 333/957 (35%) CDI from April 2008 – March 2011 were within 2 SNVs of ≥1 previous case since September 2007 (consistent with transmission). 428/957 (45%) were >10SNVs from all previous cases: these distinct subtypes continued to be identified consistently throughout the study, suggesting cases arise from a considerable reservoir of C. difficile. Surprisingly, declines in the incidence of genetically-related CDI were similar to those in genetically distinct CDI suggesting interventions not just targeting symptomatic individuals, e.g. antimicrobial stewardship, have played a significant role in recent CDI declines. Finally, the feasibility of studying asymptomatic inpatients as potential source of the unexplained transmission was investigated. This thesis provides convincing evidence, in a setting with typical CDI incidence and infection control practice, that only the minority of CDI arises from other symptomatic cases. It demonstrates that much CDI arises from genetically diverse reservoirs, with each exposure resulting in relatively few secondary cases. Future control strategies therefore need to focus on identifying these reservoirs, one of which is plausibly asymptomatic inpatients, and also on interventions that prevent the transition from exposure and colonisation to disease, such as antimicrobial stewardship.